Percepção de leigos e odontólogos quanto às assimetrias simuladas no terço inferior da face em diferentes etnias - Barbosa, Priscilla Bispo de Carvalho (2016)
The measurement of facial beauty is rather subjective, therefore when attempting to reestablish facial harmony and stomatognathic system function, one should learn the nuances of individual and ethnic characteristics of each patient, as well as their needs, in order to set an adequate treatment plan. Thus, the main objective of the present research was to compare the esthetic perception of lay people and dentists regarding asymmetries simulated in the inferior third of the face, in different ethnicities. Hence, three female models were selected (white, yellow, and black) and simulated alterations were performed in the inferior third of their faces, unilaterally, in every two degrees up to eight degrees of alteration. Finally, a total of 15 images was obtained (five of each model). A sample including 60 individuals equally divided between dentists (orthodontists, and oral-maxillofacial surgeons) and lay people evaluated these images. The images were presented in Power Point slides to the evaluators who made their analyses by answering a questionnaire that included, at first, questions regarding the level of facial pleasantness of the images presented (expressed by a numerical interval scale from zero to ten) and the need for intervention. Later, there were questions regarding what images were more and less pleasant for the same model. For data statistical analysis, the Kruskall Wallis test (p < .05) was used to assess the presence of statistical difference in the esthetic perception of the groups of evaluators regarding the degrees of facial alteration and the ethnicities used in the research; and the Mann- Whitney test (p < .05) was used to verify between which groups such difference occurred and whether the gender of evaluators had an influence on their perception of facial asymmetries. According to the statistical tests used, it was verified that orthodontists and lay people presented the same level of perception regarding facial alterations up to four degrees of deviation, orthodontists and oral-maxillofacial surgeons had a different assessment of facial alterations up to four degrees, and lay people and oral-maxillofacial surgeons had different overviews regarding the perception of facial alterations in all degrees of alteration. As for the verification of statistical difference among the ethnicities evaluated, white and yellow ethnicities presented difference in two degrees of facial alteration; white and black ethnicities presented difference in zero, two, and four degrees; and yellow and black ethnicities did not present statistically significant difference. As for the gender of the evaluator, it was found that men and women presented similar levels of perception regarding the facial deformities promoted. It was concluded that oral-maxillofacial surgeons were more skilled in detecting the facial alterations established, which suggests that the professional education provides a different overview in the perception of facial asymmetries, ethnicity plays a relevant role in the perception of facial alterations, and the gender of the evaluator had no influence in the perception of facial asymmetries.